Sepsis: An emergency medical condition and out-of-hospital diagnostic challenge - Vukićević Verica; Ilić Andrijana; Obradović Aleksandra; Milivojčević-Bevc Ivana (Halo 194)
Introduction/Objective Sepsis is, by definition, a life-threatening organ dysfunction caused by an inadequate response to infection. As such, sepsis is an emergency medical condition that must be treated in an appropriate and timely manner. Early recognition and treatment improve outcomes. The article aims to present the case of a patient suspected of sepsis at the initial pre-hospital examination, which was later confirmed at the hospital. The objective is to draw attention to the symptomatology that patients can exhibit in cases of sepsis. The patient report was supplemented with data from the literature. Case raport The patient presented was suspected of having sepsis. He was initially examined in the field and transported to the hospital while continuously monitored and treated. At the hospital, the diagnosis of sepsis was confirmed. Conclusion Sepsis should be treated like any other emergency medical condition. Timely recognition and adequate treatment are key to sepsis patients' survival. If treatment is initiated within the first hour of symptoms onset, the survival rate is over 80%. If it is initiated after six hours, the survival rate is only 30%.